Self‐reported racism and experience of toothache among pregnant Aboriginal Australians: the role of perceived stress, sense of control, and social support. (2nd July 2014) - Ben, Jehonathan; Paradies, Yin; Priest, Naomi; Parker, Eleanor Jane; Roberts‐Thomson, Kaye F.; Lawrence, Herenia P.; Broughton, John; Jamieson, Lisa M.
Abstract Objectives We hypothesized that the psychosocial factors perceived stress and sense of personal control mediated the relationship between self‐reported racism and experience of toothache. We hypothesized that social support moderated this relationship. Methods Data from 365 pregnant Aboriginal Australian women were used to evaluate experience of toothache, socio‐demographic factors, psychosocial factors, general health, risk behaviors, and self‐reported racism exposure. Hierarchical logistic regression models estimated odds ratios (ORs) and 95 percent confidence intervals (CIs) for experience of toothache. Perceived stress and sense of personal control were examined as mediators of the association between self‐reported racism and experience of toothache. Social support was examined as a moderator. Results Self‐reported racism persisted as a risk indicator for experience of toothache (OR 1.99, 95 percent CI 1.07‐3.72) after controlling for age, level of education, and difficulty paying a $100 dental bill. The relationship between self‐reported racism and experience of toothache was mediated by sense of control. The direct effect of self‐reported racism on experience of toothache became only marginally significant, and the indirect effect was significant (β coefficient = 0.04, bias‐corrected 95 percent CI 0.004‐0.105, 21.2 percent of effect mediated). Stress was insignificant as a mediator. Social support was insignificant as a moderator. Conclusions The findings indicate that high levels of self‐reported racism were associated with experience of toothache and that sense of control, but not perceived stress, mediated the association between self‐reported racism and experience of toothache among this sample of pregnant Aboriginal Australian women. Social support did not moderate the association between self‐reported racism and experience of toothache.